Spectroscopy modern concepts - Penn, Jason (NY Research Press, 2015)
This book provides substantial research on Spectroscopy. Spectroscopy is the field pertaining to absorption and emission of electromagnetic radiation through the interface between matter and energy. It is based on the principle that energy varies on the particular wavelength of electromagnetic radiation. It has proven to be critical as a research instrument in multiple spheres like chemistry, physics, biology, medicine and ecology. The spheres of study are growing rapidly and scientists are delving into upcoming areas in this sphere through the introduction of novel procedures. The motive of this book is to emphasize on the current spectroscopic techniques like Nano Spectroscopy and Optical Spectroscopy. The book also covers organic and physical spectroscopy. The text is a great source of knowledge for education and research functions.